New Inequalities for Nielsen's Beta Function - Nantomah, Kwara (Communications in Mathematics and Applications, 2019)
By employing the classical mean value theorem, Hermite-Hadamard inequality and some other analytical techniques, we establish some new inequalities for Nielsen's beta function. Some of these inequalities provide bounds for certain ratios of the gamma function.